al-Tawkīd fī Sūrat al-Kahfi, wa-Maryam, wa-Ṭāha: Dirāsah Taḥlīlīyah Naḥwīyah - Muhammad Kamal bin Abdul Hakim; Raden Ahmad Barnabas; Kaisah Mushilah (Universitas Negeri Jakarta, 2019)
This research aims to analyze the contents of the statement about emphasis (tawkīd) on sūrat al-Kahfi, Maryam, and Ṭāha. The used method in this research is a qualitative descriptive method and used a classification table to specify the explanation. Tawkīd is an affirmation language style that useful to emphasize expression and eliminate hesitation. Tawkīd is used for emphasizing certainty and causing it accepted in the listener’s mind and heart. Based on data analysis conducted by the researcher, deduced that on sūrat al-Kahfi, Maryam and Ṭāha found 58 kinds of tawkīd. 55 (95%) were tawkīd lafẓī, and 3 (5%) were tawkīd ma‘nawī. Besides, they found 154 different kinds from the articles of tawkīd which is divided into 8 types. Those were 8 (5%) of lām, and 51 (32%) of innā, and 13 (8%) of annā, and 23 (15%) of qad, and 21 (13%) of sīn or sawfa, and 18 (12%) of lan, and researchers were not found the type lām juḥūd from the kinds of tawkīd articles.